Reconfigurable enhanced path metric updater unit for Space Time Trellis Code Viterbi decoder - Abu, Mohd Azlan; Harun, Harlisya; Harmin, Mohammad Yazdi; Abdul Wahab, Noor Izzri; Rahmat, Mohd Khairil; Abd Hamid, Mohd Fairuz; Ramli, Aizat Faiz (Penerbit Universiti Teknikal Malaysia Melaka, 2017)
Space Time Trellis Code (STTC) encoding and decoding techniques are effective for delivery of a reliable information because of the signal to noise ratio is very small. Even though the Viterbi algorithm is complicated to be designed, these methods typically used large memory space to store the information that have been processed mainly at the Path Metric Updater (PMU). Therefore, an effective memory management technique is one of the key factors in designing the STTC Viterbi decoder for low power consumption applications. This paper proposed the PMU memory reduction technique especially on Traceback activities that usually required a lot of memories for storing the data that has been processed in the past part by using Altera Quartus 2 and 0.18 µm Altera CPLD 5M570ZF256C5 as targeted hardware. Through this method, the reduction achieved at least 66% of memory requirements and 75% improvements in processing time without a significant effects on the outputs results of the STTC Viterbi Decoder for 4-PSK modulation technique by using 50MHz clocks.